Studi Perbandingan Pengelolaan Usaha Perikanan Jaring Terapung di DAS Citarum (Waduk Jatiluhur, Saguling dan Cirata) Jawa Barat - Lusi Fausia; Popong Nurhayati; Wawan Okatriza; Moch Prihatna Sobari (Buletin Ekonomi Perikanan, 1996)
The development of fish culture in DAS Citarum in concentrated in Jatiluhur, Saguling and Cirata reservoirs. The main objective of these fish culture development in those three reservoirs is over come the job occupations lost of the farmers located in that areas due to the reservoir establisment. In order to develop the fish culture system, which is relatively still new, a lot of improvement is still required especially in terms of its management and technological aspects. Due to these condision, an analysis of this business is necessary to ber conducted in order so provide some information for development. This study shows that profit gained from the fish culture in these reservoir are Rp 1.495.400/pond/year in Jatiluhur. Rp 1.680.200/pond/year in Saguling and Rp 1.485.560/pond/year in Cirata.